Level and distribution of heavy metals in Miri River, Malaysia - Amit Kumar Maharjan; Dick Rong En Wong; Rubiyatno Rubiyatno (Tecno Scientifica Publishing, 2021)
Heavy metal pollution in water resources has become a serious and hazardous environmental problem all over the world because of its non-biodegradability, emanating from multiple sources, easy accumulation, and biological toxicity. This research was carried out to study the level and distribution of heavy metals at different sampling locations (upstream, midstream, and downstream), at different depths (0.5 m and 1.5 m from surface water level), and during low tide and high tide conditions in the Miri River of Miri City in Malaysia. The river water samples were collected and analyzed for Ca, Mg, Cu, Fe, Mn, Ni, Pb, and Zn by flame atomic absorption spectrophotometer. The concentration of Ca was found to be the highest in the Miri River, followed by Mg and Fe, and with traces of Cu, Mn, Ni, Pb, and Zn. An increase in the concentration of heavy metals, such as Cu, Mg, and Ni, was observed while flowing from upstream to downstream of the Miri River. Concentrations of heavy metals, such as Ca, Mg, Cu, and Zn, were clearly lower at 1.5 m depth than at 0.5 m depth. High tides in the river decrease the concentration of heavy metals, such as Ca, Cu, Mn, and Ni, compared to low tides. From this research, it gets clear that using the Miri River water for domestic and recreational purposes, washing, and fishing is detrimental to human health and the environment.